Determination of the geometric design parameters of pillow-plate heat exchangers. (5th December 2015) - Piper, M.; Olenberg, A.; Tran, J.M.; Kenig, E.Y.
Abstract: Pillow-plate heat exchangers (PPHE) are characterized by their wavy "pillow-like" surface and fully welded construction. They represent a promising alternative to conventional heat exchangers and are commonly encountered as condensers in the process industry. However, in contrast to conventional devices, there are no reliable design methods available for PPHE in the literature, which hinders expansion of PPHE application. In this study, a determination method for the hydraulic diameter, cross-sectional area and heat transfer area is proposed for pillow-plate geometries. The method is based on forming simulations, which accurately reproduce the inherently three-dimensional wavy pillow-plate channels by imitating the real manufacturing process of pillow plates. The simulation results are then used to develop simple expressions for the geometric design parameters. Graphical abstract: Highlights: The wavy pillow-plate surface was accurately reproduced by forming simulations. Useful expressions for hydraulic diameter and heat transfer area were developed. A detailed PPHE design can now be performed in a straightforward way.